The effects of an immersive virtual reality and telemedicine-based multi-component intervention in individuals with subjective cognitive decline: study protocol of a randomized controlled trial - De Simone, Maria Stefania; Zabberoni, Silvia; Costa, Alberto; Tenaglia, Erika; Tieri, Gaetano (Frontiers in Psychology, 2025)
BackgroundOlder adults with subjective cognitive decline (SCD) are at high risk of developing dementia and frequently experience subclinical symptoms (e.g., anxiety, depression) which are themselves associated with an increased dementia and cognitive decline risk. Our aim is to test the effects of an immersive virtual reality (IVR) and telemedicine-based multi-component intervention, that combines cognitive training and health and lifestyle education program, in individuals with SCD.MethodsTo assess the efficacy of the intervention, a randomized, double-blinded controlled trial will be conducted on a sample of 75 individuals with SCD. Participants will be randomly assigned to one of three conditions: (a) multi-component intervention, including SCD-tailored cognitive IVR training plus a health and lifestyle education program, (b) cognitive-only intervention, including SCD-tailored cognitive IVR training plus an active control for the education program, and (c) active control intervention for both cognitive training and education program. All interventions are implemented in IVR environment and will be administered through telemedicine approach. Interventions will be provided in 20 at-home sessions (4 sessions/week, each lasting about 30 min) over a period of 5 consecutive weeks. Outcome measures will be collected before and immediately after intervention. The primary outcome is the effect of the multi-component intervention in enhancing objective cognitive functioning. Secondary outcomes include changes in subjective cognitive functioning, psychiatric symptoms, quality of life and functional neural connectivity. Users' compliance with IVR and telemedicine approach will be also evaluated, as well as individuals' factors affecting training efficacy.DiscussionOur results will provide new evidence of the efficacy of an innovative multi-component intervention integrating IVR and telemedicine in SCD individuals. Considering the relatively low costs and easy accessibility, it could be a valuable contribution to primary prevention initiatives for dementia risk reduction.Trial registrationThis trial was prospectively registered at ClinicalTrials.gov on May 24, 2024 (registration number: NCT06429215).